Profil Ekonomi Rumahtangga Nelayan Di Desa Kota Bani Kecamatan Putri Hijau Kabupaten Bengkulu Utara - Anggraeni, Ani; Nusril, Nusril; Arianti, Nyayu Neti (MuJAgri: Musamus Journal of Agribusiness, 2023)
This study aims to analyze: 1) The characteristics of fishermen's business in Kota Bani Village, Putri Hijau District, North Bengkulu Regency, and 2) The income structure of fisherman households in Kota Bani Village, Putri Hijau District, North Bengkulu Regency. This research method was carried out deliberately with 20 active fishermen in Kota Bani Village as respondents. The results showed that the business profile of fishermen business in Kota Bani Village included the transportation equipment used was a boat with a weight of 15 PK, as much as 80% of fishermen used fishing nets and fishing rods, the average number of fishermen working days was 20 days/month with 7 hours/day, 60% of fishermen choose Senabah Seblat Harbor because it is near (200-500 m from where they live), the distance to the sea is 4.25 miles, involving family members to help, and active fishermen in fishing groups for an average of 5 years. The average income of fisherman households is IDR 15,728,000/month which is contributed by three sources of income, namely from fishing activities at 87.81%, from agricultural activities (rice and oil palm) at 2.65%, and from non-agricultural activities at 9.54%.